EFEKTIFITAS PENGGUNAAN PERANGKAT MULTIMEDIA TERHADAP PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK BERKESULITAN BELAJAR - Faiz Noormiyanto (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
AbstractÂ This study aims to determine the Effectiveness of the Use of Multimedia Devices on Improving Learning Achievement of Students with Learning Difficulties in Class IV Flat Material SD Bromantakan No. 56 Surakarta Academic Year 2011/2012. The method used in this study is an experimental method with experimental design One group pretest -post test design, in which a group of subjects is subject to treatment for a certain period of time, and the effect of the treatment is measured by the difference between the initial measurement (pre-test) and final bookkeeping (post-test). The population is students with difficulty learning to write grade IV SD Bromantakan No. 56 Surakarta, amounting to 5 children. The sample in this study was not used because the population was small, so all children were subjected to the study. Data collection techniques using test techniques, namely test description to measure the ability to write beginning. This study uses a non-parametric statistical analysis method, the Wilcoxon Signed Rank Test . From the results of the descriptive analysis it can be obtained that the average post-test score is greater than 72.40 than the pre-test average value of 39.20. The results of the non-parametric analysis obtained the value of Z = -2.023 with P = 0.042. Thus the hypothesis reads that there is a significant influence of the use of multimedia on improving the learning achievement of students with learning difficulties in the grade IV flat material of SD Bromantakan No. 56 being accepted. The conclusion of the study states that there is a significant influence of the use of multimedia on improving the learning achievement of students with learning difficulties in class IV flat material SD Bromantakan No. 56Keywords: Learning Difficulties, Multimedia, Media, LearningÂ